Doświadczenia kulturowe społeczeństwa utrwalone w związkach frazeologicznych – aspekt pedagogiczny - Kuszak , Kinga (Studia Edukacyjne, 2020)
The article discusses the cultural experience preserved in language in the form of more or less popular phrasemes. The author identifies selected sources of the phrasemes and depicts their function in preserving and saving the cultural heritage of past generations. She highlights the changes taking place in the contemporary language. The author underlines the multidirectional nature of these changes: on the one hand, society preserves the linguistic heritage, while on the other hand it gives new meanings to previously known words and sayings, creates new words and phrasemes which allow a reflection on the current socio-cultural experiences of individuals and social groups. The summary indicates the educational aspect of the issue and the necessity of implementing a carefully planned native language education which will support developing the identities of individuals, social groups and society as a whole.